1988
DOI: 10.1002/fld.1650080403
|View full text |Cite
|
Sign up to set email alerts
|

Examination of pressure oscillations arising in the computation of cascade flow using a boundary‐fitted co‐ordinate system

Abstract: SUMMARYThe incompressible flow through a two-dimensional cascade is computed using the SIMPLE algorithm in a boundary-fitted co-ordinate system, With the standard staggered grid arrangement the numerical solution was found to allow localized pressure oscillations to persist adjacent to the periodic boundaries. These oscillations were found to be a consequence of the extended momentum control volumes which are required in this region of the cascade. Such control volumes may be removed by the use of appropriatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Consequently, an iterative pressure-velocity correction is carried out similar to that followed in MAC method. The work of Lapworth (1988) which points out the prime difficulty in dealing with highly skewed bodyfitting grids, arising in the form of pressure oscillations is worth mentioning. The problem is very much similar to the checkerboard oscillation problem in computations involving non-staggered grids.…”
Section: Computational Difficulties Associated With Highly Skewed Gridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an iterative pressure-velocity correction is carried out similar to that followed in MAC method. The work of Lapworth (1988) which points out the prime difficulty in dealing with highly skewed bodyfitting grids, arising in the form of pressure oscillations is worth mentioning. The problem is very much similar to the checkerboard oscillation problem in computations involving non-staggered grids.…”
Section: Computational Difficulties Associated With Highly Skewed Gridsmentioning
confidence: 99%
“…Mostly staggered grids were employed for computations using body-fitted coordinates having staggered Cartesian as well as physical velocities. Lapworth (1988) identified the trouble associated with conventionally staggered grids in the form of pressure oscillations arising in flow computations involving highly skewed meshes. He reported that for highly skewed meshes such as those used for computing flow past turbine blades, the cells on the computational plane no longer follow the directional sense of the discretized differential terms on staggered physical grids.…”
Section: Introductionmentioning
confidence: 99%
“…The elliptic nature of the solution is obtained by repeating complete marching sweeps of the flow field until a converged solution is obtained. The present three dimensional elliptic calculation procedure is a direct extension of the two dimensional procedure developed by Lapworth (1988) The geometry of the Ghost impeller and the five measurement stations used by Johnson (1979) are illustrated in Fig. 2a.…”
Section: Numerical Solution Schemementioning
confidence: 99%
“…Hence, the present Ghost computations are a natural precursor to a study of Eckardt's impeller in which the effects of compressibility and tip leakage are significant. The present three dimensional flow model has been developed from the two dimensional elliptic model used by Lapworth (1988) to compute cascade flows. The numerical model solves finite volume approximations to the primitive variable flow equations using the SIMPLE algorithm (Patankar and Spalding, 1972) in an arbitrary generalised coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, nonstaggered (or colocated) discretization is much more widespread for the Navier-Stokes equations than staggered discretization and prevails in commercial codes. An incomplete list of publications taking this route is [23,25] (one-sided discretization of div u and grad p); [1,2,9,19,20,29,35,40,45,46,51,52,59,61,62,96] (using the pressure-weighted interpolation method of Rhie and Chow [61]); and [4,10,12,21,34,43,44,50,49,60,63,65,64,72,77,80] (employing artificial compressibility). But for incompressible flows, a price has to be paid for the ease of handling general coordinates that nonstaggered discretization brings.…”
Section: Introductionmentioning
confidence: 99%